Calculation of the BEM Integrals on a Variable Grid With the FFT - Benad, Justus (Frontiers in Mechanical Engineering, 2020)
In this study, an exemplary application of the pFFT is shown for the 2D Navier equation for a linear elastic continuum. Using this example, it is illustrated how the pFFT might be extended in order to decrease the computational complexity of the method. In the standard pFFT approach, all panel influences which are not calculated directly are obtained using a single regular grid. In the present study, a variable gird is suggested to obtain these influences. It is outlined how it is possible to apply the FFT on each level of this variable grid by rearranging segments of the shape boundary. A brief example is presented which indicates feasibility of the concept.